Evaluación de la accesibilidad al transporte público en la parroquia Barbones - Lopez Barba, Jose Manuel (Machala : Universidad Técnica de Machala, 2024)
Public transportation accessibility in rural areas is a critical challenge in Latin America and Ecuador, affecting the economic, social, and territorial development of communities. In the rural parish of Barbones, located in the El Guabo canton, poor mobility has been identified on Avenida 6 de Agosto, caused by factors such as a lack of planning and vehicle control. This situation restricts pedestrian and vehicular traffic, impacting connectivity and the quality of life of its residents. This study aims to assess public transportation access in the Barbones parish by gathering information on collective transport to propose strategies that optimize mobility conditions in the area. To achieve this, a mixed-method approach was applied, combining qualitative and quantitative methodologies through field observation and surveys conducted with 365 people. Public transportation access was evaluated using the PTAL method and the Accessibility Index (AI). The results revealed significant deficiencies in public transportation infrastructure, with inadequate bus stops that fail to meet INEN 2292 regulatory standards and unequal access to the service. Consequently, many residents must walk more than 1 km to reach a stop. The accessibility level analysis yielded an average score of 1b, classified as “very poor,” indicating low efficiency and coverage of public transportation in the area. To address this issue, it is necessary to improve the planning and distribution of public transportation services in Barbones, prioritizing route expansion, bus stop improvements, and the implementation of measures that ensure more efficient and equitable mobility.
La accesibilidad al transporte público en zonas rurales es un desafío crítico en Latinoamérica y Ecuador, afectando el desarrollo económico, social y territorial de las comunidades. En la parroquia rural Barbones del Cantón El Guabo, se ha identificado una movilidad deficiente en la avenida 6 de agosto, ocasionada factores como falta de planificación y control vehicular, lo que limita el tránsito de peatones y vehículos, impactando la conectividad y calidad de vida de sus habitantes. Este estudio tiene como objetivo evaluar el acceso al transporte público en la parroquia Barbones mediante el levantamiento de información sobre el transporte colectivo, con el fin de proponer estrategias que optimicen las condiciones de movilidad en la zona. Para ello, se aplicó una metodología mixta, combinando enfoques cualitativos y cuantitativos a través de observación de campo, encuestas a 365 personas con lo que se evaluó el nivel de acceso al transporte público mediante el método PTAL y el Índice de Accesibilidad (IA). Los resultados evidenciaron que la infraestructura de transporte público presenta deficiencias significativas, con paradas inadecuadas que no cumplen con los estándares normativos INEN 2292 y un acceso desigual al servicio, lo que obliga a muchos habitantes a recorrer distancias superiores a 1 km para alcanzar una parada. El análisis del nivel de accesibilidad arrojó un promedio de 1b, catalogado como “muy malo”, indicando una baja eficiencia y cobertura del transporte público en la zona. Para abordar esta problemática es necesario mejorar la planificación y distribución del servicio de transporte público en Barbones, priorizando la expansión de rutas, la mejora de paradas y la implementación de medidas que garanticen una movilidad más eficiente y equitativa.
Keywords: MOVILIDAD URBANA; ZONAS RURALES; ACCESIBILIDAD; TRANSPORTE PUBLICO